Bi-allelic variants in KCNU1 cause impaired acrosome reactions and male infertility. Issue 7 (11th May 2022) - Liu, Ruyi; Yan, Zheng; Fan, Yong; Qu, Ronggui; Chen, Biaobang; Li, Bin; Wu, Ling; Wu, Haibo; Mu, Jian; Zhao, Lin; Wang, Wenjing; Dong, Jie; et al.
Abstract: STUDY QUESTION: Are there new genetic factors responsible for male infertility with normal sperm quantity and morphology? SUMMARY ANSWER: We identified the bi-allelic variants in KCNU1 and confirmed it a novel pathogenetic gene for male infertility mainly due to impaired sperm acrosome reactions (ARs). WHAT IS KNOWN ALREADY: Until now, the underlying genetic determinants for male affected individuals exhibiting normal sperm quantity and morphology have been largely unknown. Potassium/calcium-activated channel subfamily U member 1 (KCNU1) is a sperm-specific potassium channel. The Kcnu1 null mutation in male mice causes infertility due to the impaired progressive motility and AR. STUDY DESIGN, SIZE, DURATION: We recruited a cohort of 126 male infertility individuals with typical asthenospermia or fertilization failure and focused on two infertile males from two consanguineous families from 2015 to 2020; whole-exome sequencing and homozygosity mapping were performed. We identified a homozygous missense variant (c.2144A>G, p.His715Arg) and a homozygous donor splice-site variant (c.1295 + 3A>C, p.Val405Glyfs*8) in KCNU1 . Then, we generated a knock-in (KI) mouse model in September 2020 and have now carried out functional studies and possible treatment strategies. PARTICIPANTS/MATERIALS, SETTING, METHODS: The affected individuals with infertility were recruited from the Shanghai Ninth Hospital affiliated to Shanghai Jiao Tong University. Genomic DNA from the affected individual was extracted from peripheral blood. Whole-exome sequencing, homozygosity mapping and in silico analyses were used to screen and identify KCNU1 variants, and the variants were confirmed by Sanger sequencing. We used C57BL/6N mouse to construct KI mouse model to mimic the reproductive phenotype in vivo . We performed functional experiments by western blotting, AR assay and immunofluorescent Staining. Finally, we performed IVF and ICSI to explore the treatment strategies. MAIN RESULTS AND THE ROLE OF CHANCE: We identified a homozygous missense variant (c.2144A>G, p.His715Arg) and a homozygous donor splice-site variant (c.1295 + 3A>C, p.Val405Glyfs*8) in KCNU1 in two infertile males. We demonstrated that the splice-site variant affected normal alternative splicing of KCNU1, thus leading to the loss of function of KCNU1. Meanwhile, the missense pathogenic variant reduced the KCNU1 protein levels in sperm of both the affected individual and the KI mouse model, resulting in impaired ARs and male infertility. Intracytoplasmic sperm injection was able to rescue the deficiencies. LARGE SCALE DATA: N/A  LIMITATIONS, REASONS FOR CAUTION: The exact molecular mechanism of KCNU1 and pathways need to be further explore in the future. WIDER IMPLICATIONS OF THE FINDINGS: This is the first report that establishes a causal relationship between KCNU1 deficiency and male infertility, confirming the critical role of KCNU1 in human reproduction. Our findings expand our knowledge of the genes that play critical roles in the human sperm AR and provide a new genetic marker for infertility. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by the SHIPM-pi fund no. JY201801 from the Shanghai Institute of Precision Medicine, Ninth People's Hospital Shanghai Jiao Tong University School of Medicine, the National Natural Science Foundation of China (81725006, 81771649, 81822019, 81771581, 81971450, 81971382, 82001538 and 82071642). The authors declare no conflict of interest. TRIAL REGISTRATION NUMBER: N/A.